Porin activity of the native and recombinant outer membrane protein Oms28 of Borrelia burgdorferi. - Skare, J T (1996)
The outer membrane-spanning (Oms) proteins of Borrelia burgdorferi have been visualized by freeze-fracture analysis but, until recently, not further characterized. We developed a method for the isolation of B. burgdorferi outer membrane vesicles and described porin activities with single-channel conductances of 0.6 and 12.6 nS in 1 M KCI. By using both nondenaturing isoelectric focusing gel electrophoresis and fast-performance liquid chromatography separation after detergent solubilization, we found that the 0.6-nS porin activity resided in a 28-kDa protein, designated Oms28. The oms28 gene was cloned, and its nucleotide sequence was determined. The deduced amino acid sequence of Oms28 predicted a 257-amino-acid precursor protein with a putative 24-amino-acid leader peptidase I signal sequence. Processed Oms28 yielded a mature protein with a predicted molecular mass of 25,363 Da. When overproduced in Escherichia coli, the Oms28 porin fractionated in part to the outer membrane. Sodium dodecyl sulfate-polyacrylamide gel-purified recombinant Oms28 from E. coli retained functional activity as demonstrated by an average single-channel conductance of 1.1 nS in the planar lipid bilayer assay. These findings confirmed that Oms28 is a B. burgdorferi porin, the first to be described. As such, it is potential relevance to the pathogenesis of Lyme borreliosis and to the physiology of the spirochete.